Pattern of Injuries among Dog Bite Victims in an Urban Area of Kancheepuram District, Tamilnadu - Charulatha RJ; Umadevi R; Ananthaeashwar VM (Medsci Publications, 2021)
Introduction: Rabies is a fatal zoonotic disease caused by bite of an infected animal, dogs being the most common reservoir of the virus. India accounts about 59.9 % of rabies death in Asia. The site of bite, depth of the wound and health seeking behavior among the victims play a major role in the prevention and effective management of rabies Objectives: To study the pattern of injuries among dog bite victims in an urban area of Kancheepuram district, Tamilnadu. Methodology: A community based cross-sectional study was conducted among 120 victims who visited a tertiary care veterinary hospital followed by a dog bite. They were selected by convenient sampling method. Data collected was analyzed statistically using SPSS 25.0 version. Result: In this study, the most common site of bite was lower limbs (62.0%). Prevalence of bite by stray dogs was high (56.2 %). Immediate post - exposure prophylaxis with soap and water was practiced by 78.5 %. Around 82.6% knew that it is preventable Conclusion: Health education about rabies vaccination and appropriate management measures with intersectoral coordination and community participation needed to achieve the target of zero human death from dog mediated rabies by 2030.